Nilai Pendidikan, Sosial, Kultural, dan Spiritual dalam Wasiat Renungan Masa Karya Tgkh. Zainuddin Abdul Madjid: Tinjauan Hermeneutika - Abdul Nasip; Mahyuni Mahyuni; Nuriadi Nuriadi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
The Testament of Devotional Period is one type of literary work in the form of poetry by TGKH. Zainuddin bin Abdul Madjid, the founder of Nahdlatul Wathan (NW) organization in Lombok. The purpose of this study is to explore character education values in the testament using hermeneutic theory of Hans-George Gadamer. Primary data of this study were values in the text of testatment and the secondary data were results of review of literature, and results of interview. Results show values ​​contained in the testament include: character education, social, cultural, and spiritual, with character education as the dominant value. Factors that cause the dominance of the value of character education in the testament include: effort to maintain the existence of NW, fostering the attitude of sami'na waata'na to NW alumni, a tool to suggest fighting spirit for NW, heirs of the Prophets, and fostering fanaticism towards NW.